HUBUNGAN TIDUR LARUT MALAM DENGAN PENUAAN DINI PADA DOSEN POLITEKNIK NEGERI BALI JURUSAN PARIWISATA - Fitria Ningrum, Nurmalia; Pangkahila, J. Alex (E-Jurnal Medika Udayana, 2017)
The aging process is a process that occurs in every human being old it is inevitable dependent and run at different speeds. Some researchers have argued about theories of aging one of which is the free radical theory and the wear and tear that is most often a factor in the aging process, aging process involves a decrease in organ function followed with increasing age means increasing the length of time working these organs. With the phenomenon is then conducted research on the relationship to sleep late with premature aging of Bali State Polytechnic Lecturer of the Department of Tourism. This research is an analytic study to find a relationship between them. This study uses primary data consists of 37 samples consisted of 25-50 years of age. Found results decreased function of muscle endurance, physical endurance, emotional control, and elasticity of the skin on the respondent who sleep late with the results of the Pearson Correlation 1 (p> 0.01.) It is considered significant. Further research is needed to determine the relationship more closely about the aging process. Keywords : Sleep late at night, early aging